Non-noble metal anode based dual-ion batteries： promising high-energy and low-cost energy storage devices - Tang, Zhiyong (Science China materials, 2017)
Lithium-ion batteries （LIBs）, as one of the most commonly used electrochemical energy storage devices, have domi- nated today＇s markets for portable electronics and electric vehicles [1]. However, their energy density cannot yet satisfy the increasing requirement, so it is imperative for de- veloping next-generation batteries with high energy den- sity together with long cycling life and good safety.